PENGARUH PENGGUNAAN PENDEKATAN REALISTIC MATHEMATIC EDUCATIONTERHADAP HASIL BELAJAR MATEMATIKASISWADI SEKOLAH DASAR - Nabila, Nasrin; Margiati, KY; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this reasearch is to analyze effect of applying realistics mathematics education approach to students in Primary School. The method used is the experimental method.This research using Quasi Experimental Design with form Nonequivalent Control Group Design. The sample of this research are all students in grade V MIS NU II Pontianak with a total of 54 students. The data collection technique is a measurement technique. The average learning outcomes of final test class V A is 65,48 and class V Bis 76,16 gained tarithmetic (1,8835)>ttable ?=5% (1,67), then Ha acceptable. So, it can be concluded that there is an influence of application the realistics mathematics education approach to the learning outcomes of mathematic in Primary School. Based on the results of the calculation of the effect size obtained 0,79 which is classified in the high category, , this case mean applying realistics mathematics education approach gives a high influence on the learning outcomes of mathematic in MIS NU III. Keywords: Influence, Realistic Mathematic Education Approach, Learning Outcomes Of Students, Matahematic